2020
DOI: 10.1002/mame.202000487
|View full text |Cite
|
Sign up to set email alerts
|

Micromechanical Behavior of TPMS Scaffolds for Bone Tissue Engineering

Abstract: The triply periodic minimal surfaces (TPMS) methodology is explored to design porosity and curvature‐controlled tissue engineering (TE) scaffolds. This work combines mechanical testing and finite element (FE) simulation to characterize TPMS scaffolds micromechanical behavior, i.e., to estimate the response at the cell level to the macromechanical properties of different geometries (Schwartz D, Gyroid, and Schwartz P, with 60%, 70%, and 80% porosity, identified from SD60 to SP80) and testing conditions (6%, 8%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…Porosity is also the main determinant for the amount of strain in the scaffold when an external force is applied according to both micro-FE analyses and experimental characterisation ( Hannink and Arts, 2011 ; Castro et al, 2020 ). If under pressure/compressive force loading through bioreactors, a scaffold with a lower porosity (i.e.…”
Section: The Role Of Scaffold Pore Geometry On the Cell Micro-mechanical Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Porosity is also the main determinant for the amount of strain in the scaffold when an external force is applied according to both micro-FE analyses and experimental characterisation ( Hannink and Arts, 2011 ; Castro et al, 2020 ). If under pressure/compressive force loading through bioreactors, a scaffold with a lower porosity (i.e.…”
Section: The Role Of Scaffold Pore Geometry On the Cell Micro-mechanical Environmentmentioning
confidence: 99%
“…Under mechanical compression, the pore shape can have a distinct influence on the overall structural stiffness of the scaffold ( Castro et al, 2020 ; Jahir-Hussain et al, 2021 ). According to their calculations, the triangular pore shape resulted in the highest structural stiffness of the scaffold and the spherical pore shape resulted in the lowest stiffness among the various pore shapes (spherical, cubic, hexagonal and triangular).…”
Section: The Role Of Scaffold Pore Geometry On the Cell Micro-mechanical Environmentmentioning
confidence: 99%
“…Permeability has been demonstrated to be essential for cellular growth, with more permeable scaffolds generating more favourable conditions [10]. However, it should be highlighted that high permeability scaffolds also present some limitations, namely, lower overall mechanical properties and the reduction of the cell–scaffold interaction [11]. This is because high permeability is normally caused by high porosity, which might not allow sufficiently long entrapment of the cells inside the scaffold.…”
Section: Current Applications Of Cfd In Btementioning
confidence: 99%
“…Studies have shown that, during the scaffold design process, small changes to the pore size and/or porosity might considerably influence the scaffold's mechanical support and the process of cell growth and tissue infiltration [10,11]. Other factors that might also influence scaffold properties are the materials and manufacturing techniques that are chosen [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to structural analysis, a number of computational methods have been applied to simulate and predict mechanical performance, permeability and tissue formation in 3D printed tissue engineered devices. 1,4,8,16,23,26 Additionally, computational mechanical tests can contribute to the design verification phase of the patient specific device design control development process. 15 Predicting the mechanical performance of a design is dependent on intrinsic properties of materials used in the manufacturing process as well as the specific manufacturing process.…”
Section: Introductionmentioning
confidence: 99%